Strategy Analysis Of Cost Of Production In Determining The Price Of Corn In PT. Jagung Indonesia During Pandemic Covid 19 : Strategi Analisis Harga Pokok Produksi Dalam Penentuan Harga Jual Jagung Pada PT. Jagung Indonesia di Masa Pandemi Covid 19 - Arifin, Syamsul; Ainurrokhmah, Maghda fauzia; Kamalia, Putri Ulfa; Apriliyanto, Danang; Muhtar (Procedia of Social Sciences and Humanities, 2022)
This study aims to determine the calculation of the company's cost of goods manufactured in determining the selling price and knowing the calculation/determination of the product selling price applied by the company. This type of research is descriptive qualitative. The data sources of this research are the main director and financial admin of PT Jagung Sumber Rejeki. Data collection techniques used interviews and observations about the cost of goods manufactured. The data analysis technique used was data reduction, data presentation, conclusion and verification. Based on this research, PT Jagung Sumber Rejeki does not calculate the cost of production because the price of raw materials and the number of products purchased from farmers varies, in determining the selling price the company only looks at the current market price and in determining the selling price there will be bargaining between the company and the working partners for the basis of determining the selling price so that the selling price is obtained on the basis of an agreement between the two.